Airport responsibility for wildlife management - Rillstone, Douglas J. (Legal research digest (Airport Cooperative Research Program) ;, 2013)
"Compiles the laws and regulations pertaining to wildlife hazard management and discusses mitigation techniques applicable to airport operators."